Peran Integrasi Akademik dalam Memediasi Pengaruh Faktor Ekonomi, Faktor Sosial, dan Kesempatan Kerja terhadap Minat Melanjutkan Pendidikan S2 (Studi pada Mahasiswa Pendidikan Akuntansi FEB Unnes Angkatan 2020) - Dewi Sekar Ayu, Dewi Sekar Ayu; Setiyani, Rediana (Business and Accounting Education Journal, 2025)
The aim of this research is to examine the role of academic integration in mediating the influence of economic factors, social factors, and employment opportunities on concerns in furthering Master's education (case study of Accounting Education Students, Faculty of Economics and Business, Semarang State University class of 2020). This research takes a quantitative approach. The research population consisted of all 164 Accounting Education students from the Faculty of Economics and Business at Semarang State University’s Class of 2020. The research sample of 115 was calculated using the Isaac and Michael formula. The sampling technique is a random sampling technique. The data collection is conduced using  Google form-based questions. Data analysis techniques included  descriptive statistical analysis, t statistic test, and Sobel test. According to the research show that academic integration in mediating the influence of economic factors, social factors, and employment opportunities on concerns with continuing postgraduate education.